2015
DOI: 10.1016/j.cct.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

A store-based intervention to increase fruit and vegetable consumption: The El Valor de Nuestra Salud cluster randomized controlled trial

Abstract: Introduction Most evidence-based interventions to improve fruit and vegetable (FV) consumption target individual behaviors and family systems; however, these changes are difficult to sustain without environmental support. This paper describes an innovative social and structural food store-based intervention to increase availability and accessibility of FVs in tiendas (small-to medium-sized Latino food stores) and purchasing and consumption of FVs among tienda customers. Methods Using a cluster randomized con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 36 publications
0
45
0
Order By: Relevance
“…Given the number of interactions observed during a single 10-minute shopping trip, a typical 30-minute shopping trip may involve six or more interactions. Thus, it is important to consider the impact that directing these interactions toward healthier food and beverage choices could have on dietary intake given the frequency with which people visit these stores (Ayala et al, 2015; Sanchez-Flack et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Given the number of interactions observed during a single 10-minute shopping trip, a typical 30-minute shopping trip may involve six or more interactions. Thus, it is important to consider the impact that directing these interactions toward healthier food and beverage choices could have on dietary intake given the frequency with which people visit these stores (Ayala et al, 2015; Sanchez-Flack et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…directly collected checkout scanner data, commercially available data sets and grocery receipts) have been used to monitor the effectiveness of interventions in a variety of types of retail food stores, [9][10][11][12] including a number of recent small-store studies. [13][14][15][16][17] Together, these studies suggest that sales data can actually be used in the design of retail food interventions. For example, Foster and colleagues 9 found that low-cost strategies focussed on improving product availability and placement enhanced sales of some foods and beverage categories (milk, water, frozen meals) but not others (regular soda, diet soda, cereal).…”
Section: Introductionmentioning
confidence: 94%
“…El Valor was a clustered randomized controlled trial that used structural and social intervention strategies to modify the physical and social environments of tiendas to improve FV consumption among Latino/Hispanic customers [30]. The trial included 16-pair matched tiendas in San Diego County, California where approximately 33% of the population is of Latino/Hispanic origin [31].…”
Section: Design and Settingmentioning
confidence: 99%